Metamorphosis from Upstream to Downstream as a Strategy to Increase Turnover - ENDAH RIANAWATI, DWI; Puspasari, Ismayantika Dyah (Universitas Nusantara PGRI Kediri, 2025)
Research aim: The purpose of this study is to analyze the marketing strategy applied by Toko BmB Puring Kediri to increase product sales. Design/Methode/Approach: This research uses a descriptive qualitative approach. Where I got information by conducting interviews to business places and interviews with 2 informants, namely business owners and store management. Research Finding: The background of the formation of the BmB Puring Shop business began in 2020. The informant's business is engaged in the field of leaf ornamental plants, namely puring ornamental plants. How to set the price at the BmB Puring Shop depends on the type of id sold because different ids have different prices, in addition to that judging from the size of the puring and the color of the menor, the more menor, the more expensive the price. Meanwhile, the advantage of this BmB Puring Store that differentiates it from other stores is the quality of the products it sells. How to market puring products in this store through the tiktok live e-commerce platform. The distribution of the product is carried out directly to consumers without intermediaries of collectors or wholesalers. Meanwhile, the delivery of this puring product itself has reached outside Java and Bali. Theoretical contribution/Originality: This research is expected to be able to add information in the field of marketing strategy, especially for MSMEs of the puring type of ornamental plants. This research also provides additional insights in the field of economics, especially in the field of marketing to increase sales turnover. Practitionel/Policy implication: For MSME owners, this research is expected to provide recommendations and information related to the strategy to increase turnover applied in the business. For readers, this research is expected to be an additional source of reference for those who are interested in topics regarding marketing strategies to increase sales turnover. Meanwhile, for local governments, this research is expected to provide input or solutions in formulating MSME marketing strategy policies. As well as encouraging the government to continue to support the sustainability of MSMEs, especially in the puring ornamental plant industry sector in Kediri Regency. Research limitation: The limitation in this study is the lack of complete sales information data because the business owner has not done bookkeeping between the incoming and outgoing money used to produce this puring plant.